Análise do perfil da dívida ativa tributária na Cidade de Fortaleza: aspectos geográficos e econômicos - Nunes, Mário Cesar Chaves (2024)
This present study aims to generate information for the design of public policies to improve the effectiveness of tax collection, by evaluating the determinants of active tax debt filed related to the Tax on Urban Land Property in the municipality of Fortaleza with data between 2018 and 2022. In this setting, two distinct methodological approaches were applied. The first is based on the spatial analysis of the volume of active debt filed between the neighborhoods of Fortaleza, comparing it with the distribution of the estimated population. The evidence found suggests a positive relationship between the population level and belonging to the former Regional Executive Secretariats 2 and 6 with the volume of active debt filed in the neighborhood. The second approach uses two econometric models to define the determinants of the volume of active debt filed by neighborhoods, which are estimated by MQO and MQG. The results found suggest positive effects on the volume of active debt filed by the resident population, belonging to Integrated Security Areas 3 and 4 and the former Regional Executive Secretariats 2 and 6.